Female migrant labor domestic helpers in Singapore - Amarles, Bienvenida M. (Philippine Journal of Public Administration, 1990)
It is undeniable that the country has been exporting a growing number of female overseas workers, majority of which serve as domestic help, mainly because of the economic crisis the country is facing. However, the "filipina" (spelled with a small "f", which is supposed to mean domestic help) in pursuit of a better future abroad, is confronted with various labor problems like underpayment and sexual abuse among others. The government recognizes its responsibility over the plight of female migrant workers particularly in Singapore. To fully implement the policies in order to protect the filipinas from unfair and abusive labor practices, two issues need to be resolved: (1) the dominance of market vs. welfare considerations; and (2) the absence of Bilateral Labor Agreement.